Carbon Nanotube Transmitter-Receiver System For Hydrocarbon Exploration - Ahmad Badruzzaman B Ahmad Sallehim, Ahmad Badruzzaman (2010)

(untitled)
The main objective of this project is the development of transmitter-receiver prototype. The design is based on Horizontal Electric Dipole (HED) which consist an electric field and the magnetic field which are perpendicularly to each other.